The chemical composition influence of oil products on the efficiency of carbon-oxidizing microorganisms cultivation - Гладченко, Л. М.; Матвєєва, О. Л.; Омельчук, С. О. (Problems of Environmental Biotechnology, 2017)
An investigation was made of the ability to grow microorganisms in conditions of water pollution with oil products. The study of the destructive activity of carbon-oxidizing microorganisms Penicillium crysogenиm, Pseudomonas syringae, and Bacillus subtilis has shown that they are capable to grow in oil contamination conditions, namely synthetic motor oil of grade ZIC XQ 5W-30 and mineral motor oil of grade MD 15W-40. The most active destructor of oil products in this experiment is Bacillus subtilis microorganisms, whose biomass gain on mineral motor oil is 55,4%. A different sensitivity of oil destructor microorganisms to the chemical composition of oil products is set, which is determined by the natural characteristics of the strains.